Population fluctuation of Helopeltis antonii Signoret on cashew Anacarcium occidentalle L., in Java, Indonesia - Siswanto; Muhamad Awang, Rita; Omar, Dzolkhifli; Elna Karmawati (Universiti Putra Malaysia Press, 2008)
Population fluctuation of Helopeltis antonii was studied in a cashew smallholding in Wonogiri, Indonesia for two years beginning March 2004 to May 2006. Observation of H. antonii population was carried out systematically on 60 sample plants in 2 ha cashew smallholding every two weeks for 2 years in relation to the number of shoots and inflorescence, number of damaged shoots, inflorescence and fruits. Local rainfall, temperature and relative humidity, number of natural enemies, and fruit yield harvested were also considered. The H. antonii population fluctuated in a cyclical pattern with the peak population in July. The population began to increase at the end of the rainy season and was high during periods of low and intermittent rainfall. No insects were found during high rainfall. Number of shoots and inflorescences of cashew significantly influenced the number of H. antonii population. This trend of population abundance was not directly associated with rainfall, but rainfall influenced the physiology of shoot flushes and inflorescence production. Results of correlation and regression analysis showed that rainfall is not significantly correlated to H. antonii population and does not significantly contribute to the number of H. antonii population on cashew. However, the availability of food in the form of number of shoots and inflorescence positively correlated with the abundance of H. antonii population. The analysis between rainfall and number of shoots and inflorescence revealed that these parameters were negatively correlated. This indicated that rainfall did not directly influence the number of H. antonii population, but appears to influence the number of shoots and inflorescence.